A New Approach for the Modification of Paper Surface Properties Using Polyoxometalates - Saraiva, Mikhail S. (2010)
A new approach for the chemical modification of the surface of paper based on the application of colloidal mixtures containing cationic starch and polyoxometalates on uncoated base paper is presented. Polyoxometalates with the Keggin-type structure and physical properties similar to those presented by coating pigments, namely H3PW12O40·23H2O, H4SiW12O40·24H2O, and K7PW11O39·9H2O, have been used in order to improve the quality of inkjet printing. The analysis of the different samples by FTIR-ATR spectroscopy showed the presence of the polyoxometalates (and the cationic starch) on the top surface of the paper. In addition, the determination of surface energy parameters, namely the polar component (σsp) and the dispersive component (σsd) of the surface energy, by contact angle measurements revealed that, for the new samples, the polar component level was much higher than that of the uncoated base paper. The quality of inkjet printing, evaluated by parameters such as the gamut area and the optical density, was considerably improved by these surface treatments